Pemberdayaan Generasi Milenial Dalam Memulai Bisnis di Era Digital - Dade Nurdiniah; Iren Meita; Indra Wijaya (LPMP Imperium, 2023)
This Community Service Activity was carried out with the aim of providing training to the millennial generation in finding inspiration to start their business and motivating participants to be able to start their business by utilizing digital media or existing platforms. In addition, the millennial generation should be able to grow creativity and be able to think creatively to create a business or business opportunity, and be able to calculate the cost of products and the selling price of the products produced so that they can provide benefits for success. The activities are divided into 3 stages of training and are both bold and alluring. The training implementation method uses the service learning method approach through three stages, namely preparation, training and evaluation. The final result of this training was an increase in the proportion of correct answers in the pre-test and post-test implementation and there was a partner satisfaction level of 89%, very satisfied and 11% satisfied.